Extensively Current Activity of Transposable Elements in Natural Rice Accessions Revealed by Singleton Insertions - Liu, Zhen; Zhao, Han; Yan, Yan; Wei, Ming-Xiao; Zheng, Yun-Chao; Yue, Er-Kui; Alam, Mohammad Shah; Smartt, Kwesi Odel; Duan, Ming-Hua; Xu, Jian-Hong (Frontiers in Plant Science, 2021)
Active transposable elements (TEs) have drawn more attention as they continue to create new insertions and contribute to genetic diversity of the genome. However, only a few have been discovered in rice up to now, and their activities are mostly induced by artificial treatments (e.g. tissue culture, hybridization etc.) rather than under normal growth conditions. To systematically survey the current activity of TEs in natural rice accessions and identify rice accessions carrying highly active TEs, the transposon insertion polymorphisms (TIPs) profile was used to identify singleton insertions, which were unique to a single accession and represented the new insertion of TEs in the genome. As a result, 10,924 high-confidence singletons from 251 TE families were obtained, covering all investigated TE types. The number of singletons varied substantially among different superfamilies/families, perhaps reflecting distinct current activity. Particularly, eight TE families maintained potentially higher activity in 3,000 natural rice accessions. Sixty percent of rice accessions were detected to contain singletons, indicating the extensive activity of TEs in natural rice accessions. Thirty-five TE families exhibited potentially high activity in at least one rice accession, and the majority of them showed variable activity among different rice groups/subgroups. These naturally active TEs would be ideal candidates for elucidating the molecular mechanisms underlying the transposition and activation of TEs, as well as investigating the interactions between TEs and the host genome.